Socio-ecological instrumentalization and the economic objectives of public procurement law - Horubski, Krzysztof (Społeczno-ekologiczna instrumentalizacja a cele ekonomiczne prawa zamówień publicznych, 2021)
According to the law of the European Union, the freedoms of the single market (free movement of goods, capital and of people (workers), freedom of establishment and freedom to provide services), coexist with the obligations of Member States to achieve environmental objectives, protect vulnerable social groups against discrimination and exclusion, as well as to ensure a high level of employment. This competition between the EU policies undoubtedly necessitates the determination of how public procurement as a legal institution (an area of activity of the widely understood state) can be used to achieve instrumental (social, environmental) objectives, aside from its primary goal, i.e. maximizing the direct economic benefit from a public contract. This paper, within the scope of the abovementioned problem, analyses relevant judgments of the Court of Justice of the European Union, as well as opinions with regard to these judgments presented by legal experts on public procurement. In effect, the phenomenon of increasing socio-ecological instrumentalization of public procurement law (seemingly the direction towards which this regulation is aimed), was demonstrated in light of the selected examples.
Ekonomia XXI Wieku = Economics of the 21st Century, 2021, Nr 24, s. 27-38
Keywords: public procurement law; social and ecological instrumentalization; primary and secondary objectives; prawo zamówień publicznych; społeczna i ekologiczna instrumentalizacja; pierwotne i wtórne cele